2000
DOI: 10.1007/s002560000228
|View full text |Cite
|
Sign up to set email alerts
|

Chronic post-traumatic osteomyelitis of the lower extremity: comparison of magnetic resonance imaging and combined bone scintigraphy/immunoscintigraphy with radiolabelled monoclonal antigranulocyte antibodies

Abstract: Acute activity in a chronic osteomyelitis can be excluded with high probability if the MRI findings are negative. In the first postoperative year fibrovascular scar cannot be distinguished accurately from reactivated infection on MRI and scintigraphy may improve the accuracy of diagnosis. MRI is more sensitive in low-grade infection during the later course than combined BS/IS. Scintigraphic errors due to ectopic, peripheral, haematopoietic bone marrow can be corrected by MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
8

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 14 publications
2
57
0
8
Order By: Relevance
“…After a surgical intervention due to fracture or osteomyelitis, similar signal intensities and enhancement pattern may also persist for up to 12 months. 15,16 In four other donors (24%), MRI showed a different morphology with signal decrease in T2-weighted and signal increase in T1-weighted images (Figure 2), reflecting a local replacement of hematopoietic tissue by fat marrow. The proportion of donors with fatty marrow conversion and scleroses as residual MRI abnormalities ('long-term pattern') increased to over 70% in two-time donors.…”
Section: Discussionmentioning
confidence: 99%
“…After a surgical intervention due to fracture or osteomyelitis, similar signal intensities and enhancement pattern may also persist for up to 12 months. 15,16 In four other donors (24%), MRI showed a different morphology with signal decrease in T2-weighted and signal increase in T1-weighted images (Figure 2), reflecting a local replacement of hematopoietic tissue by fat marrow. The proportion of donors with fatty marrow conversion and scleroses as residual MRI abnormalities ('long-term pattern') increased to over 70% in two-time donors.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, MRI lacks specificity, especially in the post-surgery setting or in diabetic foot alterations. Kaim et al [30] reported a sensitivity, specificity, and accuracy of 100%, 69%, and 78% for MRI in chronic post-traumatic osteomyelitis. Today, CT scans are better for the visualization of sequestra and are less expensive than MRI.…”
Section: Radiologic Imagingmentioning
confidence: 99%
“…29,34,47,59,[62][63][64][65][66][67][68][69][70][71][72][73] These studies have also been the subject of review 20,33,51,74,75 and retrospective data analysis, 29,76 and 80 inflammatory bowel disease, [81][82][83] and septic loosening of knee 84 or hip 85 endoprosthesis, although a detailed discussion of such uses extends beyond the scope of this report. Beyond diagnosis of infection and inflammation, bone marrow scintigraphy has been used to track bone metastases in cancer patients 86,87 and has also been considered for radiotherapeutic applications.…”
Section: Imaging Inflammation and Infection In Patients With Suspectementioning
confidence: 99%
“…These false-positive and false-negative results support the conclusions of a number of groups that scintigraphy is a powerful tool when used in conjunction with other modern imaging modalities, such as MRI or CT, and histologic examinations. 9,29,76 Finally, Guhlmann et al 47 Tc]MDP bone scan were investigated, and two expert readers analyzed the data. They concluded that although both methods were suitable for diagnosis of chronic osteomyelitis in the peripheral skeleton, FDG-PET was superior (accuracy, 96% vs 96%; sensitivity, 100% vs 97%; and specificity, 95% vs 95%) to [ 99m Tc]besilesomab (accuracy, 82% vs 88%; sensitivity, 86% vs 92%; and specificity, 77% vs 82%).…”
Section: Imaging Inflammation and Infection In Patients With Suspectementioning
confidence: 99%
See 1 more Smart Citation